Comparison of Hematological and Biochemical Profiles of Late Pregnant and Non-Pregnant Mares - Yazlik, Murat Onur; Dikmeoglu, Ezgi; Esen, Arzu; Kaya, Ufuk; Kafkas, Özgenur; Baran, Burak; Göcen, Murat (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
The maternal body must adapt to fetal growth and development during the state of pregnancy for successful foal and mother. Pregnancy status as in other mammals is related to physiology and hematology. This study aimed to compare the hematology profiles and biochemical parameters of late pregnant and non-pregnant mares. Twenty-two mares were included in the study. Mares were divided into two groups according to the pregnancy status. Hematology profile and biochemical parameters were analyzed from blood samples collected from the jugular vein. All data were analyzed using Stata 12/MP4. White blood cell count, lymphocyte, red blood cell count, hemoglobin concentration, hematocrit, monocyte and percentage of monocyte were significantly lower in non-pregnant mares compared to late pregnant mares (P<0.05). No significant differences were noted in values of neutrophil, eosinophil, mean cell volume, mean corpuscular hemoglobin concentration, mean corpuscular hemoglobin, platelet, mean platelet volume, red cell distribution width in both groups (P>0.05). On the other hand, biochemical parameters analysis showed that calcium, total bilirubin, and triglyceride concentrations were greater in late pregnant mares (P<0.05). However, urea, albumin, cholesterol, and magnesium concentrations were similar among groups (P>0.05). In conclusion, the present study showed hematology profile and biochemical parameters differences in late pregnant and non-pregnant mares. These values could be useful in clinical practices to assess the situation of late pregnant mares.